Effect of monthly high-dose vitamin D supplementation on falls and non-vertebral fractures: secondary and post-hoc outcomes from the randomised, double-blind, placebo-controlled ViDA trial. Issue 6 (June 2017) - Khaw, Kay-Tee; Stewart, Alistair W; Waayer, Debbie; Lawes, Carlene M M; Toop, Les; Camargo, Carlos A; Scragg, Robert
Summary: Background: Adults with low concentrations of 25-hydroxyvitamin D (25[OH]D) in blood have an increased risk of falls and fractures, but randomised trials of vitamin D supplementation have had inconsistent results. We aimed to assess the effect of high-dose vitamin D supplementation on fractures and falls. Methods: The Vitamin D Assessment (ViDA) Study was a randomised, double-blind, placebo-controlled trial of healthy volunteers aged 50–84 years conducted at one centre in Auckland, New Zealand. Participants were randomly assigned to receive either an initial oral dose of 200 000 IU (5·0 mg) colecalciferol (vitamin D3 ) followed by monthly 100 000 IU (2·5 mg) colecalciferol or equivalent placebo dosing. The prespecified primary outcome was cardiovascular disease and secondary outcomes were respiratory illness and fractures. Here, we report secondary outcome data for fractures and post-hoc outcome data for falls. Cox proportional hazards models were used to estimate hazard ratios (HRs) for time to first fracture or time to first fall in individuals allocated vitamin D compared with placebo. The analysis of fractures included all participants who gave consent and was by intention-to-treat; the analysis of falls included all individuals who returned one or more questionnaires. This trial is registered with the Australian New Zealand Clinical Trials Registry, number ACTRN12611000402943. Findings: Between April 5, 2011, and Nov 6, 2012, 5110 participants were recruited and randomly assigned either colecalciferol (n=2558) or placebo (n=2552). Two participants allocated placebo withdrew consent after randomisation; thus, a total of 5108 individuals were included in the analysis of fractures. The mean age of participants was 65·9 years (SD 8·3) and 2971 (58%) were men. The mean concentration of 25(OH)D in blood was 63 nmol/L (SD 24) at baseline, with 1534 (30%) having 25(OH)D concentrations lower than 50 nmol/L. Follow-up was until July 31, 2015, with a mean treatment duration of 3·4 years (SD 0·4, range 2·5–4·2). During follow-up, 2638 participants reported having a fall, 1312 (52%) of 2539 in the vitamin D group compared with 1326 (53%) of 2517 in the placebo group. The HR for falls—adjusted for age, sex, ethnic origin, history of recent fall, physical activity, and baseline 25(OH)D—was 0·99 (95% CI 0·92–1·07; p=0·82) for vitamin D compared with placebo. Non-vertebral fractures were reported in 292 individuals, 156 (6%) of 2558 in the vitamin D group and 136 (5%) of 2550 in the placebo group. The adjusted HR for fractures was 1·19 (95% CI 0·94–1·50; p=0·15) for vitamin D compared with placebo. 123 (2%) people died during the trial, 65 assigned vitamin D and 58 allocated placebo; the difference between treatment groups was not significant. Interpretation: High-dose bolus vitamin D supplementation of 100 000 IU colecalciferol monthly over 2·5–4·2 years did not prevent falls or fractures in this healthy, ambulatory, adult population. Further research is needed to ascertain the effects of daily vitamin D dosing, with or without calcium. Funding: Health Research Council of New Zealand and Accident Compensation Corporation of New Zealand.